Shielding effectiveness measurement of cement-graphite block in between 3.8 GHz to 6 GHz - Yeoh, S. L.; Yee, S. K.; T. J. Ong, N.; Dahlan, S. H.; Sia, C. K. (Bulletin of Electrical Engineering and Informatics, 2020)
Due to proliferation of electronic devices, the electromagnetic field (EMF) exposure affect human health in long term. On the other hand the operation electronic devices will be affected if the radiation level is too high. To reduce the radiation exposure, shielding is always used. Instead of building a shielding enclosure inside a building, it is more practical to improve the shielding capability of the building itself. Hence, this project intend to investigate the shielding effectiveness (SE) of cement added with graphite. Eight cement-graphite specimens with different percentages (0%, 3%, 7%, 11%, 15%, 19%, 25% and 30%) are prepared. They have been casted into the waveguide mold with size of 4.75 cm x 1 cm x 2.22 cm and taken for measurement directly. The SE measurement setup involve a pair of waveguide with frequency range of 3.8 GHz to 6 GHz and vector network analyser (VNA). Throughout the study, it is found that the percentage of graphite powder will affect the SE of the specimens. The SE is independent on its curing duration. More than 11% of graphite is needed to improve the SE of cement block in between 3.8 GHz to 6 GHz. The highest SE of 33 dB is achieved when the sample contains 30% of graphite with thickness of 1cm.